Tense, abilities and actuality entailment - Mari, Alda; Martin, Fabienne (Proceedings of the Amsterdam Colloquium, 2007)
In French as in other languages diffentiating the perfective and the imperfective morphologically, modal verbs sometimes behave like implicative verbs in perfective sentences. We present new data that previous accounts cannot explain. The offered analysis relies on a distinction between classical abilities and what we call action dependent abilities.